Do vegetarians feel bad? Examining the association between eating vegetarian and subjective well-being in two representative samples. (December 2020) - Pfeiler, Tamara M.; Egloff, Boris
Highlights: The present study aimed to examine the association between vegetarianism and subjective well-being in two large representative samples from Germany and Australia. Results of t -tests showed that vegetarians reported slightly higher scores in negative affect (Study 1 and 2), but also slightly higher levels of satisfaction with health (Study 1 and 2) and life satisfaction (Study 1) compared to meat eaters. These differences between vegetarians and meat-eaters in some components of SWB, although significant due to the large sample sizes, are small at best ( d around 0.15). Because sex, age, and education were associated with diet type and SWB, analyses controlling for socio-demographic variables were also conducted. Taken together, the very small effects found in the t -tests for some components of SWB seem to be due to socio-demographic variables, meaning that the true effects of diet on SWB are non-existent or negligible. Abstract: Research on the relationship between vegetarianism and subjective well-being (SWB) has produced inconsistent results, which may partly be due to small sample sizes and divergent operationalizations of well-being. For these reasons, the present study aimed to thoroughly examine this association in two large representative samples from Germany (Study 1: N  = 12, 905, including 665 vegetarians) and Australia (Study 2: N  = 15, 532, including 383 vegetarians) using a consensual conceptualization of SWB (composed of an affective component, i.e., positive and negative affect, and a cognitive component, i.e., life satisfaction). Results of t -tests showed that vegetarians reported slightly higher scores in negative affect (Study 1 and 2), but also slightly higher levels of satisfaction with health (Study 1 and 2) and life satisfaction (Study 1) compared to meat eaters. No differences emerged regarding positive affect in either study. These differences between vegetarians and meat-eaters in some components of SWB, although significant due to the large sample sizes, are small at best ( d around 0.15). Because sex, age, and education were associated with diet type and SWB, analyses controlling for socio-demographic variables were also conducted. In these ANCOVAS, the effect of diet emerged only for one out of the five formerly significant comparisons (negative affect in Study 1, d  = 0.09) while the differences between vegetarians and meat eaters in both satisfaction with health and life, as well as the effect on negative affect in Study 2, all became non-significant ( d around 0.05). Taken together, the very small effects found in the t -tests for some components of SWB seem to be due to socio-demographic variables, meaning that the true effects of diet on SWB are non-existent or negligible.